It's in his kiss - Quinn, Julia, 1970- (Quinn, Julia, 1970- Bridgerton series., 2021)
Hyacinth Bridgerton offers to translate an old family diary for Gareth St. Clair, but as they delve into the mysterious text, they discover that the answers they seek are not in the diary, but in each other.